Book review: Kostelecky, Sarah R., Townsend, Lori and Hurley, David A. Hopeful visions, practical actions: cultural humility in library work - Elena Maceviciute (Information Research: An International Electronic Journal)
Kostelecky, Sarah R., Townsend, Lori and Hurley, David A. Hopeful visions, practical actions: cultural humility in library work. London: Facet Publishing, 2023. xxiii, 236 p. ISBN 978-1-78330-633-6